A COMPARATIVE STUDY BETWEEN TRANSABDOMINAL AND TRANSVAGINAL ULTRASOUND TECHNIQUES IN EARLY DETECTION OF ECTOPIC PREGNANCY (The Research of Medical Science Review, 2025)
Background:Ectopic pregnancy is a potentially life-threatening condition that necessitatestimely and accurate diagnosis to prevent serious complications. Ultrasonographyis important in detecting this condition early. Although the transabdominalultrasound is non invasive and frequently used in a clinical setup, thetransvaginal ultrasound has better resolution and much of the organs within thepelvis are well seen during examination. This research paper will seek to comparetwo diagnostic tests transabdominal and transvaginal ultrasound, to detectectopic pregnancies at the early stages of gestation.Objectives: This study will aim at assessing and comparing the diagnosticeffectiveness of transabdominal and transvaginal ultrasound in the earlydiagnosis of ectopic pregnancy and establish which of the two modalities ofultrasound examination is more efficient in the early diagnosis stage to providebetter clinical outcomes to women in the early gestations.Study design: A Cross sectional study.Place and duration of study: From 25 November 2024 to 24 May 2025Department of Diagnostic Radiology, Bolan Medical College/Hospital, Quetta.Methods: The present was cross-sectional study with a sample size of 82 patientswho presented with a suspected case of the ectopic pregnancy in a tertiary carehospital. All subjects were subjected to transabdominal and transvaginalultrasound investigations that were conducted by senior radiologists. The finaldiagnosis was done on the basis of clinical data, beta-human chorionicgonadotropin. content in serums, and results of surgeries. Diagnostic performanceof the two imaging modalities was carried out through statistical methods byusing SPSS version 24.0 software and in particular statistical measures ofsensitivity and specificity were considered.Results: The average age of the 82 patients was 27.8 +/- 4.6 years.Transvaginal ultrasound made the correct diagnosis of ectopic pregnancy in 74cases (90.2%), whereas transabdominal ultrasound diagnosed 62 cases (75.6%).TVUS had a higher sensitivity and specificity of 92.5 and 88.0, respectively,than TAUS, which was 78.4 and 81.0, respectively. The diagnostic accuracy difference was statistically significant (p = 0.003). TVUS also proved to havesuperior visualization of adnexal masses and free pelvic fluid. These resultssubstantiate the use of TVUS as a better diagnostic modality in early detection ofectopic pregnancy.Conclusion: Transvaginal ultrasound demonstrates superior performance in theearly detection of ectopic pregnancy when compared to transabdominalultrasound, offering enhanced sensitivity, specificity, and diagnostic accuracy. Itshigh-resolution imaging facilitates the identification of subtle adnexalabnormalities and the presence of free pelvic fluid, making it the modality ofchoice in routine clinical practice. Incorporating transvaginal ultrasound into thediagnostic workup for suspected ectopic pregnancy can substantially improveearly diagnosis and clinical outcomes, particularly in emergency care settings.